The trend analysis of Islamization in Malaysia using Islamization index as indicator - Wan Omar, W. A.; Hussin, Fauzi; Golam Hassan, Asan Ali (Asian Economic and Social Society, 2014)
This paper empirically analyses the trend of Islamization in Malaysia using the Islamization Index as an indicator to determine whether the time series dataset of the Islamization index possess deterministic trends or stochastic properties.The result determines the appropriateness of the employment of the Islamization index as a proxy of Islam in the empirical study of Islam and economic performance such as economic growth and development, and not as a spurious relation as in the case of the non-stationary stochastic trend.